Children's spirituality and the practice of meditation in Irish primary schools - Keating, Noel (International journal of children's spirituality, 2017)
This paper uses an interdisciplinary approach to explore the child's experience of meditation in Irish primary schools and its impact on children's spirituality. Using a phenomenological, hermeneutic, mystagogical methodology, it describes how children experience the practice of meditation, the benefits they consider they gain from it and the nature of its impact, if any, on their spirituality. Seventy children, aged 7 to 11, were interviewed. The study is original in that the interview protocol contained novel processes designed to elicit from children their experience, if any, of the transcendent in meditation and in its depth of analysis of the spiritual fruits of the practice. The study concludes that meditation does have the capacity to nourish the innate spirituality of the child. It offers a heuristic model outlining the key elements of the child's experience of meditation, stresses the importance of personal spiritual experience and supports the introduction of meditation in primary schools.